Dinamika Urban Sufisme di Indonesia: Continuity and Change dalam Majelis Shalawat Muhammad di Surabaya - Rubaidi Rubaidi (Islamica: Jurnal Studi Keislaman, 2017)
This paper discusses the phenomenon of urban sufism among the majelis Shalawat Muhammad under the murshid Gus Kahar in Surabaya with followers (disciples) spreading in various places especially East Java, even abroad. The theory of continuity and change is used to critically review Howellâ€™s concept on urban sufism, and to present key concepts on sufism in its generic sense in terms of doctrine and empirical praxis. Although based in Surabaya, the doctrine and praxis of urban sufism in the Majelis Shalawat Muhammad reflects generic sufi teachings. The findings of this research reveal that the principle of continuity and change prevails in sufi tradition from time to time. This finding is different from Howellâ€™s theory which stress on ritual dimension. The followers of Shalawat Muhammad emphasize more on education on the basis of praxis (sÄlik-sulÅ«k, riyÄá¸¥ah, and mujÄhadah), in addition to the dimension of doctrine itself.